2021
DOI: 10.1186/s13071-021-04743-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of two sexual-stage antigens as bivalent transmission-blocking vaccines in rodent malaria

Abstract: Background Transmission-blocking vaccine (TBV) is a promising strategy for malaria elimination. It is hypothesized that mixing or fusing two antigens targeting different stages of sexual development may provide higher transmission-blocking activity than these antigens used individually. Methods A chimeric protein composed of fragments of Pbg37 and PSOP25 was designed and expressed the recombinant protein in Escherichia coli Rosetta-gami B (DE3). Af… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Two studies additionally showed that the protective immunity induced by dual-antigen malaria vaccines PfCSP-Pfs25 or Pvs25-PvCSP was able to provide a promising high level of transmission-reducing activity (TRA; > 99% for PfCSP-Pfs25; 82% for Pvs25-PvCSP) [ 28 , 29 ]. Comparable to the results of these reports, in our recent work, we showed that fusing or mixing Pbg37 with ookinete surface antigen PSOP25 for immunization was able to enhance the TRA efficiency afforded by Pbg37 alone [ 30 ]. These findings provide support that dual-antigen malaria vaccines, which provide greater overall protection, cost-effectiveness and durability than a single-stage vaccine, will be a powerful tool for malaria control.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…Two studies additionally showed that the protective immunity induced by dual-antigen malaria vaccines PfCSP-Pfs25 or Pvs25-PvCSP was able to provide a promising high level of transmission-reducing activity (TRA; > 99% for PfCSP-Pfs25; 82% for Pvs25-PvCSP) [ 28 , 29 ]. Comparable to the results of these reports, in our recent work, we showed that fusing or mixing Pbg37 with ookinete surface antigen PSOP25 for immunization was able to enhance the TRA efficiency afforded by Pbg37 alone [ 30 ]. These findings provide support that dual-antigen malaria vaccines, which provide greater overall protection, cost-effectiveness and durability than a single-stage vaccine, will be a powerful tool for malaria control.…”
Section: Introductionmentioning
confidence: 53%
“…After blocking with 5% skim milk, the parasites were incubated with sera from immunized mice (dilution: 1:500) for 1 h, then co-labeled with rabbit antisera against P47 (dilution: 1:500), α-tubulin II (dilution: 1:500) or Pbs25 (dilution: 1:500) as stage-specific markers for female gametocytes/gametes, male gametocytes/gametes and zygotes/ookinetes, respectively, followed by three washing steps in PBS. The polyclonal antibodies against P47, α-tubulin II and Pbs25 were made in our laboratory [ 30 ]. Alexa Fluor 488-conjugated goat anti-mouse IgG antibodies (dilution: 1:500; Invitrogen, Thermo Fisher Scientific) and Alexa Fluor 555-conjugated goat anti-rabbit IgG antibodies (dilution: 1:500; Invitrogen, Thermo Fisher Scientific) were used as secondary antibodies.…”
Section: Methodsmentioning
confidence: 99%
“…The AP205-2*SpyTag was expressed in E. coli Rosetta-gami B (DE3) cells under induction with 1 mM IPTG (Sigma) at 20 °C for 16 h. Bacterial cells from the overnight culture were pelleted by centrifugation at 4 °C. The pellet was resuspended with a HIS-binding buffer containing 50 mM sodium phosphate buffer and 300 mM NaCl (pH 8.0) and was lysed by sonication [ 28 ]. The bacterial lysate was centrifuged, and the pellet was suspended in Buffer B solution (100 mM NaH 2 PO 4, 10 mM Tris, 8 M Urea, pH 8.0).…”
Section: Methodsmentioning
confidence: 99%
“…Negative controls were HA-tagged ookinetes incubated with the secondary antibodies alone, or WT ookinetes incubated with the anti-HA mAb. The antibodies against PbMSP1, Pbg377, α-tubulin II, and PSOP25 were made in our laboratory [ 25 ]. Parasites were visualized using a Nikon C2 fluorescence confocal laser scanning microscope (Nikon, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%